Standing on the ice: experiences of women national ice hockey players in Turkey - Doğusan Sena Nur; Koçak Funda (Sciendo, 2021)
The purpose of this phenomenological study was to examine within the framework of symbolic interaction theory and field theory how women national ice hockey players understand ice hockey through their experiences. Semi-structured interviews were used to understand the experiences of 21 ice hockey players from the Turkish women's national team, and themes were developed from the data using the thematic analysis methods. A total of three main themes and two sub-themes were created after the analysis. In this context, three main themes related to the theoretical framework were established: "Symbolic Meanings: A Strong Ice Hockey Player," "Ice Hockey As a Life Space," and "A Hard Fight On the Ice." In addition, under the main theme of "Ice Hockey As a Life Space" are two sub-themes: "World of Emotions" and "Constraints." Ice hockey is perceived by women players as a living space that expresses a firm stance towards life. Despite the presence of traces of the concept of gender, ice hockey is not seen as a fully gendered area by Turkish players. In general, women players reported the lack of financial and social support as limiting factors for participation in ice hockey, while moral support and high motivation were supporting factors.